Analysis of Improving the Quality of Fatty Acid Methyl Ester (FAME) Products Against Acid Value (AV) Levels Using the Six Sigma and Kaizen Methods - Afifi, Mohammad Salva; Dahda, Said Salim (Advance Sustainable Science, Engineering and Technology, 2024)
. PT XYZ is a palm oil derivative processing company that produces biodiesel / FAME (Fatty Acid Methyl Ester) products. However, there are several obstacles that still occur during the company's production process which causes the acid value (AV) level of FAME products to not meet specifications and there are 3% defective products. Therefore, this study aims to determine the improvement plan by applying kaizen to the Six Sigma improvement stage and reducing outspec products in the FAME production process. The results of the research conducted using the six sigma method show that the company has a DPMO value of 71,459 and a sigma value of 2.96 which is in the average position of the industry in Indonesia based on the results of data processing. While recommendations for improvement by implementing kaizen include training machine operators, making standard operating procedures (SOPs) for machine inspections on each shift, reducing the amount of strearin added to AV raw materials before pre-treatment, maintenance and machine calibration.Â  This step are expected to overcome the main problems identified in the study.